Mouse Model for Pre‐Clinical Study of Human Cancer Immunotherapy. (2nd February 2015) - Ya, Zhiya; Hailemichael, Yared; Overwijk, Willem; Restifo, Nicholas P.
Abstract: This unit describes protocols for developing tumors in mice, including subcutaneous growth, pulmonary metastases of B16 melanoma, and spontaneous melanoma in B‐Raf V600E/PTEN deletion transgenic mouse models. Two immunization methods to prevent B16 tumor growth are described using B16.GM‐CSF and recombinant vaccinia virus. A therapeutic approach is also included that uses adoptive transfer of tumor antigen–specific T cells. Methods including CTL induction, isolation, testing, and genetic modification of mouse T cells for adoptive transfer by using retrovirus‐expressing genes of interest are provided. Additional sections, including growing B16 melanoma, enumerating pulmonary metastases, tumor imaging technique, and use of recombinant viruses for vaccination, are discussed together with safety concerns. © 2015 by John Wiley & Sons, Inc.